TRADE OFF SISTEM USAHATANI TEMBAKAU DI WILAYAH SUMBING TEMANGGUNG JAWA TENGAH - Danang Manumono; Masyhuri Masyhuri; Slamet Hartono; Ani Suryantini (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2010)
Comodities farming system is the farming system management whith a commodity whose primerly planting which coverage by the sub-systems or other commodities arranged with characteristic and specificly and integrated toward that commodity. The research location in slope of Sumbing mountain which have tobacco aromatics with high nicotin and tar. The sample are sub-village to trade off phenomena analyzes with purposive sampling and the data are intensively take in sub-village farmer with proporsion sampling. And anlysis in power function regression model.Sumbing slope land area have 2 character agroclimate. High land area have longer time harvaest commodities than midle land area and have dry season whose can not planted with economic commodities except tobacco. Phenomena of trade off on high land area not happen in changing comodities farming system but not in midle land area. The tradeoff phenomena were midle land area in changging of cabbage farming system with tobacco farming system, but not for other system. Increasing of cabbage farming system area whose indicated decreasing tobacco farming system area caused decreasing in input use by farmer on that area but not for economic produktivity land.Keywords: commodity farming system, tradeoff phenomena.